The Effects of N-acetylcysteine on Inflammatory Markers and Homocysteine: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Jamal Hallajzadeh; Alireza Milajerdi; Željko Reiner; Fariba Kolahdooz; Zatollah Asemi (Tabriz University of Medical Sciences, 2020)
Background: Recently a number of trials investigated the effect of N-acetylcysteine (NAC) administration on inflammatory markers and homocysteine (Hcy). However, their findings are controversial. The aim of this paper is to present a meta-analysis and give a review of all randomized controlled trials (RCTs) in order to determine the effects of NAC on inflammatory markers and Hcy. Methods: An electronic search was conducted using PubMed, Scopus, Cochrane Library, Google scholar and Web of Science databases from inception until April 2019. A study quality assessment was performed using the Jadad scale and heterogeneity between studies was statistically computed using Cochrane's Q test and I-square (I2). Data were pooled using a random-effects model and weighted mean difference (WMD) was considered as the overall effect size. Results: Out of 1115 potential citations, 10 studies (reported 13 effect sizes for different parameters) met the inclusion criteria and were eligible for this meta-analysis. NAC supplementation resulted in a significant reduction in Hcy levels (WMD: -2.05; 95% CI: -3.73, -0.37). NAC administration did not affect C-reactive protein (CRP) levels (WMD: 0.06; 95% CI: -0.21, 0.34), tumor necrosis factor-α (TNF-α) levels (WMD: 0.07; 95% CI: -0.27, 0.40), and interleukin 6 (IL-6) (WMD: -0.23; 95% CI: -1.23, 0.77). Conclusions: It could be concluded that this meta-analysis of RCTs demonstrated that NAC administration to various patients significantly improved circulating Hcy, but did not affect CRP IL-6 and TNF-α levels.